"It's very hard, but I'll manage." Educational aspirations and educational resilience among recently resettled young refugees in Norwegian upper secondary schools. (7th December 2020) - Lynnebakke, Brit; Pastoor, Lutine de Wal
ABSTRACT: Purpose: This article explores the question:  what shapes young refugees' often high educational aspirations ? A sense of mastery and future hope are among the numerous factors that can positively predict school achievements. High aspirations may thus contribute to both young refugees' improved educational outcomes and wellbeing. Method: We discuss findings from semi-structured interviews in three Norwegian upper secondary schools in light of theories and research into the often high educational aspirations of immigrant youth.   Results: Several of the study's findings support the dual frame of reference theory which has been used in prior discussions of migrants' aspirations. However, we argue that aspirations can be supported not only by comparisons with the country of origin, but also by comparisons with different stages of the refugee experience. Conclusions: The findings suggest that temporal aspects of high aspirations should be empirically and theoretically explored further. Moreover, this and other studies' findings on young refugees suggest that research into the educational aspirations of young immigrants should address/control for migration category.